TEACHER'S EFFORTS IN IMPROVING STUDENT DISCIPLINE THROUGH THE REWARD AND PUNISHMENT METHOD IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS AT SD INPRES 2 LERE - Nanda Sumayah; Yusdin Bin. M Gagaramusu; Dyah Rahmawati; Rizal; Ammar Abdullah Joni Guci (SOSIOEDUKASI, 2026)
Student discipline in the Islamic Religious Education (PAI) subject at SD Inpres 2 Lere requires specific interventions to address varying levels of classroom compliance. This study analyzes the teacher's structural efforts in utilizing the reward and punishment method to enforce discipline and shape student behavior. Using a qualitative descriptive design, data were extracted directly from the school principal, PAI teacher, and students via non-test instruments: passive observation, structured interviews, questionnaires, and documentation. The pedagogical intervention is executed in three distinct phases: planning, implementation, and evaluation. The planning phase sets explicit classroom rules and defines the boundaries of consequences. Implementation relies on delivering positive reinforcement—such as applause, verbal praise, and tangible gifts—to compliant students, countered by educational punishments, specifically the mandatory memorization of short Quranic surahs, for infractions. The data confirms that substituting physical sanctions with educational penalties significantly modifies student conduct. Observational metrics recorded a 76.66% discipline rate, placing student compliance squarely within the "Disciplined" threshold. Corroborating this, student questionnaires scored 86.54% ("Very Good"), proving the method's reception as fair and motivating. The systematic integration of reward and punishment acts as a definitive mechanism to elevate learning motivation, curb classroom disruptions, and build a sustained, orderly environment for Islamic educational instruction.